Psychiatric Medication Changes Associated With Increased Rate of Medical Readmissions in Patients With Serious Mental Illness. Issue 3 (14th March 2021) - Germack, Hayley D.; Weissinger, Guy; Bizhanova, Zhadyra; Martsolf, Grant R.
Abstract: To identify the impact of postdischarge psychiatric medication changes on general medical readmissions among patients with serious mental illness (SMI; bipolar disorder, major depressive disorder, and schizophrenia), claims from a 5% national sample of Medicare fee-for-service (FFS) beneficiaries hospitalized between 2013 and 2016 were studied. A total of 165, 490 Medicare FFS beneficiaries with SMI 18 years or older with at least 1 year of continuous Medicare enrollment were identified. Within 30 days of discharge from index admission, 47.4% experienced a psychiatric medication change—including 75, 892 beneficiaries experiencing a deletion and 55, 713 experiencing an addition. After adjusting for potential confounders, those with a medication change experienced an 10% increase in the odds of 30-day readmission (odds ratio, 1.10; SE, 0.019; p < 0.001). Comorbid drug use disorder was also associated with an increased odds of readmission after controlling for other covariates. These findings suggest important factors that clinicians should be aware of when discharging patients with SMI.